E-coupon laundry service system (ECLYSS) / Wan Najmi Syahirah Sukri - Sukri, Wan Najmi Syahirah (2014)
Web-based application system is a program which run on a Web server and use Web pages as the user interface. Internet has become widely popular as a distributed environment for delivering services to the end users. However, the current service management functions that exist in the internet are not fully adequate. Therefore, E-Coupon Laundry Service System (ECLYSS) system is developed as a web based application in order to assist students and staffs of coop-mart in SMK Padang Saujana in managing e-coupon for laundry service. ECLYSS system enable students to make the laundry service easily by using ECLYSS. Besides that, staffs will check the quantity, weight and calculate the number of students’ clothes and record all of the infromations into the e-coupon system. The staffs also can update the status of the laundry service and the balance of e-coupon. Futhermore, e-coupon system is different with current system or manual system because e-coupon is secure, faster and reliable. The major finding of this project is based on the questionnaires that were distributed to the few of respondents. The questionnaires are consist of five construct which are in terms of interface, usability, functionality, content and security and privacy construct. The results of the evaluation indicated that interface construct shows the highest mean and standard deviation, Mean = 4.5 and SD = .776 between others construct. It shows that most of the respondents are agreed and satisfied with the interface of this system because it is suitable for all level of user. However, ECLYSS system needs further enhancement in terms of interface and functionality such as add more iconic character for interface and insert the dynamic price and make auto-update balance for e-coupon in near future by other researcher